Integrating transcriptome and metabolome to reveal the characteristics of gene expression profiles and metabolite changes of sorghum in response to cadmium treatment - Deng, Lixi; Chen, Yinhua; An, Yanlin; Zhang, Feng; Zhou, Ping; Mou, Chenghong; Chen, Yuyu (Frontiers in Plant Science, 2025)
IntroductionSorghum is one of the most important grain crops and industrial crops, and its planting environment is at risk of heavy metal pollution such as cadmium. However, the gene expression characteristics and changes in metabolic flux of sorghum in response to cadmium stress still need to be further revealed.MethodsThe glutinous sorghum variety “HongYingZi” was treated with 200 μM of cadmium acetate, and samples were collected at a total of eight time points (including the control group and 3h, 6h, 9h, 12h, 24h, 48h, and 72h after treatment) for transcriptome sequencing. The original sequencing data was filtered, aligned, assembled for transcripts, and identified for differentially expressed genes using software such as fastp, Hisat2, StringTie, and DEGseq. Meanwhile, UPLC-MS/MS was used to detect metabolites in all samples. Co-expression analysis was performed using the WGCNA R package, and the expression levels of related genes were verified by qRT-PCR.ResultsIn this study, transcriptome sequencing and metabolome analysis were performed on sorghum samples treated with cadmium. The results showed that a total of 2,299 differentially expressed genes were identified among different samples, including important transcription factors such as AP2/ERF, bHLH and MYB-related families. Although the number of differential genes among different groups varied greatly from 171 (CK vs TM3h) to 1,410 (CK vs TM9h), these differential genes were mainly significantly enriched in pathways such as metabolic pathways, arachidonic acid metabolism, and starch and sucrose metabolism. Meanwhile, metabolome detection identified 4,656 metabolites in 21 major categories. Although the total content of metabolites showed no significant difference among different samples, 68 amino acids and their derivatives, 16 flavonoids, 21 alkaloids, 92 organic acids and other differential metabolites were identified. Twelve gene modules related to amino acid content were identified through WGCNA analysis. qRT-PCR analysis showed that the expression levels of these genes were highly consistent with the transcriptome results.DiscussionOur research reveals the gene expression profiles and metabolite change characteristics of glutinous sorghum in response to cadmium treatment, which provided data support and new insights for further revealing the genetic mechanism and metabolic flux basis of sorghum in response to cadmium.